Indikatoren einer nachhaltigen Landwirtschaft im Regionalisierten Agrar- und Umweltinformationssystem fur̈ die Bundesrepublik Deutschland (RAUMIS) - Christian Julius; Christine Moeller; Bernhard Osterburg; Stefan Sieber (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– Indicators for a Sustainable Land Use in the Regionalised Agricultural and Environmental Information System for Germany(RAUMIS)According to the formulation of a political concept which centres on the principles of sustainable agricultural land use, agri-environmental aspects have gained an accretive importance within model based policy consultation. In this context, the following article illustrates the Regionalised Agricultural and Environmental Information System RAUMIS. It describes the state of development of the actual integration of agri-environmental indicators as well as analytical results and their applicatory suitability. The main intention of using indicators within RAUMIS is to achieve a differentiated illustration of environmental impacts of agricultural land use in the context of actual-state analysis and prospective simulations.
Keywords: 330; Landwirtschaft; Nachhaltige Entwicklung; Agrarpolitik; Politikberatung; Deutschland; Umwelt-Informationssystem